Enhancing foreign language acquisition among university undergraduate students through outside the classroom activities - Ismail, Muhd Zulkifli; Ismail, Zainuddin; Wan Sulong, Wan Muhammad; Othman, Mohd Sukki; Husain, Salina (2015)
This paper reports the findings of a study on the effectiveness of a foreign language acquisition non-syllabus bounded activities carried out outside the classroom. Students taking part in this study are from a local undergraduate students pursuing the Arabic language as a foreign language a specialization. The obstacles in acquiring a foreign language, especially the Arabic language are often associated with the learning environment in classroom which is not conducive for language acquisition to take place. This study which is based on action research approach is done with a pre-designed language activities outside the classroom in a more realistic and favorable environment for language acquisition. The subjects are final year students majoring in the Arabic language from the University Putra Malaysia who have completed their formal Arabic language courses offered by the university. This is the first out of a three planned activities. The data is obtained through interviews with the participants at the end of the activities. The findings show a very positive students response toward the activities. Students are also observed to have made a promising improvement in their Arabic language acquisition as compared to their performance after their formal university Arabic language courses. This is in addition to other findings which are of no less significant.